2008
DOI: 10.1159/000142141
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Subsequent Treatment of an Intermediate-Risk Paraspinal Neuroblastoma: Case Report and Review of the Literature

Abstract: Objectives: Neuroblastoma is the most common extracranial solid tumor of childhood, and the most common malignancy diagnosed during infancy. In comparison, neonatal neuroblastoma is relatively rare. Improvements in prenatal imaging and widespread use of fetal ultrasonography have led to an increased rate of prenatal diagnoses. Methods: Case report and literature review. Results: We report a case of an intermediate-risk neuroblastoma, diagnosed at 36 weeks’ gestation by ultrasound and subsequently visualized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…These young patients have a high survival probability, but almost all develop severe sequelae [ 4 , 5 ]. The discovery of a neuroblastoma associated with EC at birth is a rare event [ 6 ], as witnessed by the fact that only 0.2 % of all diagnoses of this tumour were registered by the Italian Association of Hematology and Oncology (AIEOP) Neuroblastoma Registry over a period of 10 years [ 7 ]. The literature concerning these patients is limited to a small number of mostly single-case reports [ 6 , 8 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These young patients have a high survival probability, but almost all develop severe sequelae [ 4 , 5 ]. The discovery of a neuroblastoma associated with EC at birth is a rare event [ 6 ], as witnessed by the fact that only 0.2 % of all diagnoses of this tumour were registered by the Italian Association of Hematology and Oncology (AIEOP) Neuroblastoma Registry over a period of 10 years [ 7 ]. The literature concerning these patients is limited to a small number of mostly single-case reports [ 6 , 8 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a neuroblastoma associated with EC at birth is a rare event [ 6 ], as witnessed by the fact that only 0.2 % of all diagnoses of this tumour were registered by the Italian Association of Hematology and Oncology (AIEOP) Neuroblastoma Registry over a period of 10 years [ 7 ]. The literature concerning these patients is limited to a small number of mostly single-case reports [ 6 , 8 16 ]. We describe herewith a newborn whose delivery was anticipated to the 36 th week of pregnancy for olygohydramnios and was found to have motor deficit and bladder dysfunction at birth secondary to an abdominal neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal detection is even rarer, and the paucity of reports in the literature attests to this (Table 1). [1][2][3][4][5][6][7][8] We report a case in which sonography and magnetic resonance imaging (MRI) were used in the detection and evaluation of an extra-adrenal metastatic neuroblastoma in a fetus.…”
mentioning
confidence: 99%
“…A C Because of its low incidence, few cases of extraadrenal neuroblastomas have been detected prenatally. [1][2][3][4][5][6][7][8]14 Fénart et al 15 and Sones 16 first reported the prenatal sonographic diagnosis of an adrenal neuroblastoma. Gadwood and Reynes 2 first reported a prenatally diagnosed case of an extra-adrenal neuroblastoma located in the neck of a fetus.…”
mentioning
confidence: 99%
See 1 more Smart Citation